Local Value in Management of Fish Resource and Development of Law (Studies of Bajo Tribe in Gorontalo) - Fenty U. Puluhulawa (Hasanuddin Law Review, 2015)
This article is intended to analyze the existence of local values that have become part of local wisdom prevailing in Bajo community. Type of research is legal anthropology, using interviews and focus group discussion. The results showed that the Bajo Gorontalo society, there are the local values associated with the management of fish resources in the sea. Local values mean that has been implemented since long time ago, and until this day the local values still remains valid. For the people of Bajo the values meant being a model society, thus forming a community adherence behavior in managing and treating fisheries resources in the sea, so that it becomes part of the public legal awareness. Therefore, it is important to identify the values that are still applicable and to make it as a basis for the development of laws related to fisheries, which is expected to be developed, as the expectations set forth in the legislation.